Pura Taman Wana Sari Menjadi Destinasi Wisata Spiritual di Desa Tegal Tugu: Bahasa Indonesia - Komang Edwin; I Ketut Sugihantara; I Wayan Widanan; Made Suryanatha Prabawa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Tegal-tugu Village, Gianyar, Bali, is a location rich in natural potential and strong religious values. This article proposes the development of the Spiritual Tourism of Taman Wana Sari in this village to utilize natural resources sustainably and promote environmental preservation. In this context, the article identifies potential issues that may arise, such as deforestation, habitat destruction, increased waste, and infrastructure problems. Furthermore, the article highlights the importance of planning for sustainable environmental management to unlock the tourism potential within Tegal-tugu Village in Gianyar, Bali, and effective waste management. The increase in visits is accompanied by an emphasis on improving comfortable and environmentally friendly facilities, which is the focus of this proposal. With meticulous planning, the development of the Spiritual Tourism of Taman Wana Sari can stimulate the local economy, enrich the spiritual and cultural experiences of tourists, and ensure the preservation of the unique religious and natural values in Tegal-tugu Village